Mengkaji Ritual Suin Re'u Masyarakat Oepikan Kabupaten Malaka, Timor dan Ketahanan Identitas Budaya di tengah Perjumpaan Iman - Yohana Wulandari Manek; Florens Maxi Un Bria; Viktor Doddy Sau Sasi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the tradition of respecting Suin Re'u (a sacred dagger) among the Oepikan people, Malaka Regency, Timor, and the efforts to maintain cultural identity amidst the encounter of faith. This study uses a descriptive qualitative method. Data were collected through observation, in-depth interviews, and documentation of eight informants consisting of traditional leaders, community leaders, and parish priests. The research findings indicate that respect for Suin Re'u functions as a cultural heritage that strengthens social solidarity, maintains identity, and builds communal spirituality. However, the study also identifies challenges in the form of dualism in the experience of faith, and the confusion of the younger generation in understanding the relationship between tradition and Church teachings, as well as the potential for syncretism. From the perspective of inculturation theology, the noble values ​​contained in this tradition such as respect for ancestors, communal solidarity, and concern for the environment as a cultural identity can be integrated with the Catholic faith without reducing the purity of the teachings. This study concludes that the Suin Re'u tradition, if properly understood, can serve as a means of strengthening the cultural identity of the Oepikan-Timor community and a contextual expression of the Catholic faith, provided that ongoing pastoral and catechetical support and communication between traditional and local religious leaders are considered, helping the congregation distinguish between cultural respect and religious worship.